The co-evolution of sectoral regulation and technological innovation: The case of detergents industry in Europe - Evita Paraskevopoulou (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2011)
This paper contributes to research addressing interrelationships between technological and policy changes by exploring the co-evolution of sectoral regulation and technological innovation in the detergents industry in Europe. We view as regulation an endogenously created institution that evolves over time and in alignment with other socioeconomic factors, among which we focus on technological change. We argue that the innovation and regulation processes are evolutionary processes that interact overtime and their co-evolution is facilitated by knowledgeable and purposeful agents who wish to influence their institutional environment. Given our empirical context we find that the opportunity provided to private actors to participate in the policy process, share information and collaborate, contributes to the improvement of their knowledge. In turn, improved knowledge increases the innovative potential of actors while it builds their bargaining power and increases the possibilities private actors have to influence their institutional environment. Favorable institutional conditions have been recognized as a factor conductive to innovation and in this sense, we can witness a circular and interactive relationship between the regulatory and innovation process.
Keywords: 330; regulation; technological innovation; private-public interactions